Polityka leśna w Polsce - Barczak, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Forest economy belongs to chief economic activities in many countries, as it forms basis of national ecological security stemming from strategic role played by forests. Each state keeping in mind the wealth of its citizens formulates the aims of its Forestry Policy and the ways of their achievement, aiming at various functions of the forest, including those ecological that have direct impact on the development of the natural environment, as well as the social and educational through which its beauty and goodness could be appreciated. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1192, s. 142-148